2008
DOI: 10.1071/wr08067
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of roadkill on Tasmanian highways: human management options

Abstract: Abstract. An obvious sign of potential human impact on animal populations is roadkill. In Tasmania, this impact is perceived as relatively greater than in other Australian states, and is often noted by visitors and locals alike, such that calls for management action are common in the popular press. The goal of this three-year study was to assess the frequency and distribution of species killed on Tasmanian roads. Seasonal surveys were completed along five major routes, for a total of 154 trips. Over 15 000 km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 22 publications
5
94
3
4
Order By: Relevance
“…Identifying locations of clusters of WVC is a common step preceding mitigation and conservation actions to protect wildlife from vehicle-caused mortality (e.g., Hobday and Minstrell 2008). In the present study, cluster locations were found to vary in position along study highways across years of observations.…”
Section: Mitigation Planningmentioning
confidence: 62%
See 1 more Smart Citation
“…Identifying locations of clusters of WVC is a common step preceding mitigation and conservation actions to protect wildlife from vehicle-caused mortality (e.g., Hobday and Minstrell 2008). In the present study, cluster locations were found to vary in position along study highways across years of observations.…”
Section: Mitigation Planningmentioning
confidence: 62%
“…Animals die as result of collisions with vehicles because of traffic speed, traffic volumes, seasonal changes in movement, separation of important habitat areas, occluded lineof-sight, and other factors (Barthelmess 2014;Hobday and Minstrell 2008;Litvaitis and Tash 2008). Most of the observations of dead animals made using the online, state systems described here were opportunistic and thus do not reflect actual rates of WVC on a particular roadway.…”
Section: Wildlife-vehicle Collisionsmentioning
confidence: 99%
“…Early road ecology research used roadkill to monitor changes in population (e.g., Baker et al, 2004), focused on emblematic species (e.g., Hobday and Minstrell, 2008) or examined spatial and temporal patterns in the distribution of roadkill (e.g., Taylor and Goldingay, 2004;Ramp et al, 2005). Many of these studies relied on road surveys conducted at regular intervals by trained observers (Barthelmess and Brooks, 2010;D'Amico et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 377,000 to 1,500,000 vertebrates are killed along Tasmanian roads each year (Hobday and Minstrell, 2008). Other studies have estimated single species rates of road kill ranging from 2.1 to 78.8 individuals km -1 y -1 (Freeman, 2010 and references therein;Quintero-Ángel et al, 2012).…”
Section: Impact Of Voucher Specimen Collection On Wild Populationsmentioning
confidence: 99%